Energy Cost of Common Activities in Children and Adolescents - Lyden, Kate (2012)
BACKGROUND: The Compendium of Energy Expenditures for Youth assigns MET values to a wide range of activities. However, only 35% of activity MET values were derived from energy cost data measured in youth; the remaining activities were estimated from adult values. PURPOSE: To determine the energy cost of common activities performed by children and adolescents and compare these data to similar activities reported in the compendium. METHODS: Thirty-two children (8–11 years old) and 28 adolescents (12–16 years) completed 4 locomotion activities on a treadmill (TRD) and 5 age-specific activities of daily living (ADL). Oxygen consumption was measured using a portable metabolic analyzer. RESULTS: In children, measured METs were significantly lower than compendium METs for 3 activities [basketball, bike riding, and Wii tennis (1.1–3.5 METs lower)]. In adolescents, measured METs were significantly lower than compendium METs for 4 ADLs [basketball, bike riding, board games, and Wii tennis (0.3–2.5 METs lower)] and 3 TRDs [2.24 m·s(−1), 1.56 m·s(−1), and 1.34 m·s(−1) (0.4–0.8 METs lower)]. CONCLUSION: The Compendium of Energy Expenditures for Youth is an invaluable resource to applied researchers. Inclusion of empirically derived data would improve the validity of the Compendium of Energy Expenditures for Youth.